2021
DOI: 10.1371/journal.pone.0249109
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effects of betulinic acid mediated by the activation of the AMP-activated protein kinase pathway

Abstract: Betulinic acid (BA) is a naturally arising pentacyclic triterpenoid that has anti-malarial, anti-retroviral, anti-inflammatory, and anti-cancer biological effects. More recently, it has been reported to possess anti-obesity activity mediated by the activation of AMP-activated protein kinase (AMPK). We further investigated antidiabetic activity of BA in mouse tissues at the cellular and systemic levels. We found that BA stimulated AMPK in a similar fashion to the known AMPK activators, such as 5-aminoimidazole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…It stimulates glucose uptake and modulates insulin secretion. Several alkaloids are allosteric activators of AMPK and enhance its enzymatic activity [ 45 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It stimulates glucose uptake and modulates insulin secretion. Several alkaloids are allosteric activators of AMPK and enhance its enzymatic activity [ 45 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its activation prompted upregulation of GLUT-4 and enhancement of glucose uptake, reduction in hepatic glucose production and increase fatty acid oxidation. It had been reported that triterpenes stimulate glucose uptake and glycogen synthesis through AMPK activation [ 49 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that several targets including AMPK, NRF2, autophagy regulators and FXR are to be considered for developing novel therapies for liver cholestatis and fibrosis. Thus, betulinic acid [53] (a natural pentacyclic triterpenoid), 5-aminoimidazole-4-carboxamide-1β-D-ribofuranoside (AICAR) [108], metformin [109,110], and GSK621 [111] are AMPK activators known for beneficial effects related to several diseases including diabetes, obesity, chronic inflammation, and cancer, and deserve to be investigated in the context of cholestasis [112]. In fact, recent studies identified the AMPK/FXR axis as having critical role in cholestatic liver injuries [113].…”
Section: Fxr Involvement In Autophagy During Cholestasismentioning
confidence: 97%
“…Free radicals are by‐products of metabolism that are highly toxic in high concentrations. They can cause the oxidation of amino acids, sugars, proteins, nucleic acids, and other compounds in various tissues, leading to oxidative stress and inflammation, and thus organ damage (Song et al., 2021; Wang, Wang, et al., 2018; Wang, Zhao, et al., 2018).…”
Section: Resultsmentioning
confidence: 99%